Dietary Diversity as a Dominant Factor of Energy Intake Among Breastfeeding Mothers in Depok City, Indonesia - Santoso, Cornelia Lugita; Sartika, Ratu Ayu Dewi; Fikawati, Sandra; Wirawan, Fadila; Putri, Primasti Nuryandari; Shukri, Nurul Husna Mohd (Kesmas, 2024)
Maternal nutritional needs increase during lactation. However, the energy intake of breastfeeding mothers usually still falls short of the recommended adequacy levels. This study aimed to identify the dominant factor of energy intake in breastfeeding mothers in Sawangan District, Depok City, Indonesia. This quantitative study used a cross-sectional design from July 2022 to February 2023. Energy intake, dietary diversity, and eating frequency were collected using 24-hour food recall. Other variables were collected through interviews with structured questionnaires. Data were analyzed using the Chi-square test and binary logistic regression. A total of 217 breastfeeding mothers participated in this study. This study found that 78.3% of breastfeeding mothers had inadequate energy intake. Dietary diversity (p-value = 0.032) was the dominant factor associated with the energy intake of breastfeeding mothers. Breastfeeding mothers with non-diverse food consumption were at a 2.507 times higher risk of inadequate energy intake. Energy intake in breastfeeding mothers is related to the sustainability of breastfeeding. However, most breastfeeding mothers in Sawangan District still have insufficient energy intake. Therefore, it is suggested that food supplementation for breastfeeding mothers should be included in promoting exclusive breastfeeding.